Eksplorasi Unsur Matematika dalam Tikar Adat di Kecamatan Loura, Kabupaten Sumba Barat Daya - Uma, Yohanes Toda; Maya, Alfridus; Lede, Yulius Keremata (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to explore the mathematical elements embedded in traditional woven mats (tikaradat) from Loura District, Southwest Sumba Regency. These mats, known as nopo or pandan mats, represent an important part of Sumbanese cultural heritage with deep social and aesthetic significance. Using an ethnomathematical approach, this research identifies mathematical concepts present in the form, pattern, and production process of traditional mats. Data were obtained through literature review, observation of local crafts, and hypothetical analysis based on geometric characteristics of mat weaving. The findings reveal the presence of geometry, repetition patterns, symmetry, proportion, and geometric transformations within the structure and motifs of traditional mats. These results indicate that Sumbanese traditional mats can serve as contextual mathematics learning media linking cultural knowledge with formal mathematical concepts